An investigation of the impacts of motivation on teachers’ job performance in Lokoja Local Government Area of Kogi State public secondary schools - Ayoko , Victor Olugbenga (American Journal of Social Sciences and Humanities, 2025)
The study investigated the impact of motivation on the job performance of public secondary school teachers in the Lokoja local government area of Kogi state. The purpose of this study is to examine the rate of job performance, find out the gender difference among motivated teachers and establish the impact of motivation on teachers’ job performance in public secondary schools in the Lokoja local government area of Kogi state. The study adopted a survey research design with a sample of 150 teachers randomly selected from ten public secondary schools in the state. An expert-validated instrument was used to collect relevant data on teachers’ job performance. The collected data was analyzed using a t-test analysis to test the hypotheses of differences. The outcome indicated a significant difference between the job performance of teachers who were motivated and those who were not and there is a significant gender difference among motivated teachers based on job performance. It was concluded that motivation is one of the developmental factors that sustain the continuity of an organization. Motivation improves the students’ academic outcome of the school organization such as improving teachers’ productivity for the betterment of the overall education sector.